2022
DOI: 10.1177/17411432211055327
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the business of educational leaders in times of uncertainty

Abstract: The main thrust of this paper is to explore factors from the business sector, which could inspire school leaders in terms of issue/problem formulation during their decision-making process. This conceptual paper examines diachronically and conceptually the issues of uncertainty, not only in terms of context and decision-making, but also having in mind leaders’ and leadership's main characteristics as well. The question remains whether concepts of uncertainty management practices from the business sector might o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 64 publications
0
10
0
3
Order By: Relevance
“…Furthermore, participants indicated that it is critical for school leaders to use a constant flow of clear, concise, calming, and flexible instructions pursuant to a common goal. Corresponding to a previous study, the key to agile decision making is developing solutions quickly based on correspondence with internal and external stakeholders (Pashiardis & Brauckmann-Sajkiewicz, 2022). We found that school leaders believed that clear and concise communication enabled stakeholders to trust and follow their instructions (influencer role), as well as allowed school leaders to become effective crisis leaders through the role of agile decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, participants indicated that it is critical for school leaders to use a constant flow of clear, concise, calming, and flexible instructions pursuant to a common goal. Corresponding to a previous study, the key to agile decision making is developing solutions quickly based on correspondence with internal and external stakeholders (Pashiardis & Brauckmann-Sajkiewicz, 2022). We found that school leaders believed that clear and concise communication enabled stakeholders to trust and follow their instructions (influencer role), as well as allowed school leaders to become effective crisis leaders through the role of agile decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Schools that are characterized be a clear and empathetic communication towards their employees (Harris and Jones, 2020;Pashiardis and Brauckmann-Sajkiewicz, 2022) are likely to foster a positive organizational climate, encourage innovation and promote high productivity (Chatzipanagiotou and Katsarou, 2023;Da'as et al, 2022). Based on this premise, the current study posits the following hypotheses: H1.…”
Section: Introductionmentioning
confidence: 95%
“…Clear and comprehensive information about organizational changes leads to more positive evaluations and greater cooperation (Goswick et al ., 2018; Miller et al ., 1994). Communication characterized by high employee participation, involvement and social connections fosters trust and facilitates change acceptance (Adams et al ., 2021; Alanezi, 2021; Harris and Jones, 2020; Pashiardis and Brauckmann-Sajkiewicz, 2022; Schechter et al ., 2022). Additionally, employee involvement enhances their sense of control and motivation in the work environment (Chatzipanagiotou and Katsarou, 2023; Panisoara et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Toward this path, school directors' administration furnished with entrepreneurial perspectives empowers these pioneers to see valuable changes before others and handle these changes in an inventive and imaginative structure (Pashiardis and Brauckmann-Sajkiewicz, 2020;Brauckmann-Sajkiewicz and Pashiardis, 2022). For instance, as Pashiardis and Baker (1992) did not entirely set in stone in their trial research, issues that emerge in schools can be transformed into an opportunity to the school executive.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, as Pashiardis and Baker (1992) did not entirely set in stone in their trial research, issues that emerge in schools can be transformed into an opportunity to the school executive. Nonetheless, to foster the entrepreneurial perspectives of the staff and faculty, these administrators can offer their schools adaptable environs that are accepted to make a growth opportunity for themselves and their staff by enduring the different enterprising mix-ups and disappointments of the staff (Pashiardis and Brauckmann-Sajkiewicz, 2020). These are extremely basic for school administrators to govern schools effectively.…”
Section: Introductionmentioning
confidence: 99%